2014
DOI: 10.1371/journal.pone.0094227
|View full text |Cite
|
Sign up to set email alerts
|

PFOS Induces Behavioral Alterations, Including Spontaneous Hyperactivity That Is Corrected by Dexamfetamine in Zebrafish Larvae

Abstract: Perfluorooctane sulfonate (PFOS) is a widely spread environmental contaminant. It accumulates in the brain and has potential neurotoxic effects. The exposure to PFOS has been associated with higher impulsivity and increased ADHD prevalence. We investigated the effects of developmental exposure to PFOS in zebrafish larvae, focusing on the modulation of activity by the dopaminergic system. We exposed zebrafish embryos to 0.1 or 1 mg/L PFOS (0.186 or 1.858 µM, respectively) and assessed swimming activity at 6 dpf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 68 publications
9
67
1
1
Order By: Relevance
“…All three PFC exposures resulted in an increase in swimming activity at 14 dpf, which correlates to previous studies indicating hyperactivity in zebrafish larvae exposed to PFOS (Spulber et al 2014). However, this does not correlate with the difference in total body size (PFOA significantly smaller, PFNA significantly larger, PFOS no change).…”
Section: Discussionsupporting
confidence: 90%
“…All three PFC exposures resulted in an increase in swimming activity at 14 dpf, which correlates to previous studies indicating hyperactivity in zebrafish larvae exposed to PFOS (Spulber et al 2014). However, this does not correlate with the difference in total body size (PFOA significantly smaller, PFNA significantly larger, PFOS no change).…”
Section: Discussionsupporting
confidence: 90%
“…Additional behavior effects included changes in swimming velocity (PFNA, PFOS) and thigmotaxis behaviors (PFNA, PFOS). Similar observations have been made in mammalian studies, in which exposure to PFOS in mice (0.3 mg/kg/day) induced spontaneous hyperactivity (Spulber et al, 2014) and mice exposed to 0.3 mg/kg PFOA showed changes in exploratory behavior (Onishchenko et al, 2011). Analyzing similar behavior endpoints in adult zebrafish will determine if the growth and behavior affects seen in larval zebrafish persist through adulthood as well as better understand the long term effects of PFAS exposure in our teleost model system.…”
Section: Introductionsupporting
confidence: 85%
“…As reported by Spulber et al (2014), zebrafish larvae exposed to 1 mg l −1 PFOS displayed a disorganized pattern of spontaneous activity and persistent hyperactivity. In the current study, we clearly demonstrated that 2 mg l −1 PFOS exposure at 28°C resulted in a reduced antipredator response by the fish, manifested as a higher frequency of use of the risky area, an increased percentage of time that the fish spent in the risky area, and a strong decrease in the average distance to the predator.…”
Section: Discussionsupporting
confidence: 66%